Estimates of mortality attributable to influenza and RSV in the United States during 1997–2009 by influenza type or subtype, age, cause of death, and risk status. Issue 5 (27th June 2014) - Matias, Gonçalo; Taylor, Robert; Haguinet, François; Schuck‐Paim, Cynthia; Lustig, Roger; Shinde, Vivek
<x xml:space="preserve">Abstract</x> Background Influenza and respiratory syncytial virus (RSV) cause substantial mortality from respiratory and other causes in the USA, especially among people aged 65 and older. Objectives We estimated the influenza‐attributable mortality and RSV‐attributable mortality in the USA, stratified by age and risk status, using outcome definitions with different sensitivity and specificity. Methods Influenza‐ and RSV‐associated mortality was assessed from October 1997–March 2009 using multiple linear regression modeling on data obtained from designated government repositories. Results The main outcomes and measures included mortality outcome definitions—pneumonia and influenza, respiratory broad, and cardiorespiratory disease. A seasonal average of 10 682 (2287–16 363), 19 100 (4862–29 245), and 28 169 (6797–42 316) deaths was attributed to influenza for pneumonia and influenza, respiratory broad, and cardiorespiratory outcome definitions, respectively. Corresponding values for RSV were 6211 (4584–8169), 11 300 (8546–14 244), and 17 199 (13 384–21 891), respectively. A/H3N2 accounted for seasonal average of 71% influenza‐attributable deaths; influenza B accounted for most (51–95%) deaths during four seasons. Approximately 70% influenza‐attributable deaths occurred in individuals ≥75 years, with increasing mortality for influenza A/H3N2 and B, but not A/H1N1. In children aged 0–4 years, an average of 97 deaths was attributed to influenza (A/H3N2 = 49, B = 33, A/H1N1 = 15) and 165 to respiratory broad outcome definition (RSV). Influenza‐attributable mortality was 2·94‐fold higher in high‐risk individuals. Conclusions Influenza‐attributable mortality was highest in older and high‐risk individuals and mortality in children was higher than reported in passive Centers for Disease Control and Prevention surveillance. Influenza B‐attributable mortality was higher than A in four of 12 seasons. Our estimates represent an updated assessment of influenza‐attributable mortality in the USA.